Linear Program Problem-Solving Skills Based on Sequential and Gender Thinking Styles During Online Learning - Rahmah, Adila; Mardiyana, Mardiyana; Sari S, Dewi Retno (Journal of Mathematics and Mathematics Education, 2021)
The study aims to describe linear program problem-solving skills reviewed from sequential thinking styles and genders as schools implement online learning due to the covid-19 pandemic. This research is a qualitative study that produces descriptive data. The subject of this study consisted of two male students and two female students of class XI MIPA High School MTA Surakarta. The study began by determining the study subjects using a thinking style questionnaire, followed by linear program problem-solving tests and interviews. Check the validity of the data using triangulation methods. The results show linear program problem-solving skills; 1) Sequential students of male and female concrete perform systematically and less carefully; 2) Abstract sequential male and female students collect complete data and analyze the information obtained regularly as well as female abstract sequential students strong in written decoding and symbols; 3) students' problem solving skills with sequential abstracts are higher than concrete sequential students ;4) male students with sequential thinking styles perform better at solving math problems than female students with sequential thinking styles.